La constitution du domaine de la Cité internationale universitaire de Paris - Brigitte Blanc (In Situ)
The Cité internationale universitaire de Paris was created immediately after the First World War in order to encourage exchanges between university students from around the world. According to the 1921 convention established between the city and the University of Paris, the Cité was built along Montsouris Park, on lots previously occupied by the Thiers fortifications. Starting in 1928, the rapid development of the Cité made it necessary to extend the site. Between the two world wars, segments of the neighboring town of Gentilly were progressively annexed. But in the early 1950s, projects for the creation of a boulevard périphérique – beltway – made further extension impossible. Today, construction continues, both on-site and outside the walls of the historical Cité.